Evaluating Of Customer Satisfaction On Occupational Health And Safety Equipment Repair By The Service Quality Method (Case Study : PT. Destini Marine Safety ) - Susisno, Bayu Tri; Kurniawan, Moh. Dian; Jufriyanto, Moh. (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Assessing service quality is one effective strategy for staying ahead of competitors in the field of service, especially customer satisfaction. Consumers who are pleased with the services provided by a business are more inclined to return and use the services of other companies. In this study, the service quality technique is used to examine the goals or gaps that exist between consumer expectations and customer satisfaction. This service quality analysis may be used to assess the value of interest or the gap between expectations and customer satisfaction for each feature. This survey comprised 100 people who used company services between January and November of 2022. According to the study results, all attributes on each dimension have a positive gap value, suggesting that the company's services are satisfactory. According to the dimensions, responsiveness with a gap value of 0.5475, reliability with a gap value of 0.5220, tangibles with a gap value of 0.4960, assurance with a gap value of 0.4920, and empathy with a gap value of 0.4833 have the best gap to the initial rejection. The responsiveness dimension of characteristic C4, which is the availability of people necessary to execute repairs, is the most impacting part of service quality at PT. Destini Maritime Safety.